A Story - Mirza, Akhtar (SARE: Southeast Asian Review of English, 2023)
It is a poem originally written in Urdu by the Pakistani Poet Akhtar Raza Saleemi. The poem speaks of a scene that is set in a desolate valley, surrounded by mountains, where three men are conversing with each other, but someone is listening, and the awareness of it is causing them to freeze in the form of a statue. It is an allegorical poetic tale about censorship and the panopticon.